An overview of the Constitutional Court hearing of the inner-city evictions case - Mbazira, Christopher (Economic and Social Rights in South Afric, 2007)
On 28 August 2007, the Constitutional Court heard an appeal against the decision of the Supreme Court of Appeal (SCA) in the Rand Properties case. This case concerns the eviction of poor people from dilapidated buildings in the inner city of Johannesburg. Acting in terms of section 12 of the National Building Regulations and Building Standards Act of 1977 (NBRA), the City of Johannesburg (the City) had issued eviction notices on the basis that these buildings were hazardous and not suitable for human habitation. It therefore brought an application to the High Court to enforce these notices.